OPTIMIZATION, PURIFICATION AND CHARACTERIZATION OF THERMOSTABLE CELLULASE FROM BACILLUS SUBTILIS KG10 ISOLATED FROM VIRGIN FOREST OF KOVAI KUTRALAM, COIMBATORE, INDIA - RAMALINGAM KOWSALYA; RAMASAMY GURUSAMY (International Journal of Pharma and Bio Sciences, 2014)
For the optimization of culture conditions, incubation time study of cellulase production by Bacillus subtilis KG10 was showed remarkable enzyme activity (0.24±0.01 U/ml) and protein content (43±2.83 µg/ml), after 32 h of incubation. The effects of various carbon and nitrogen sources tested; maximum cellulase production was recorded in CMC (0.24±0.01 U/ml) and yeast extract (0.35±0.02 U/ml), respectively. The effect of various pH and temperature examined, the maximum enzyme production was obtained in the pH 7.0 (0.35±0.02 U/ml) and 37°C (0.38±0.02 U/ml). The role of metal ions and NaCl concentration on cellulase production tested, among the metal ions, calcium chloride (0.40±0.01 U/ml) and 0.5% of NaCl concentration supported maximum enzyme production (0.43±0.01 U/ml). Whereas, the inoculums load 2% supported maximum (0.48±0.02 U/ml). The cellulase enzyme was purified through a two step chromatography which includes DEAE sepharose and sephadex G75 column chromatography. SDS-PAGE analysis of the purified cellulase enzyme revealed a single band with the molecular mass of 56 kDa. The pH stability studies revealed that purified cellulase was 100% stable over a broad pH range of 6–11 for 12 h. The optimum temperature was 50°C. However, the temperatures of 55, 60 and 65°C, the purified cellulase exhibited 92, 87 and 75% residual activity. The zymogram and biostoning of the cellulase enzyme activity effectively degraded and removed cellulose and stain, respectively.